PSM Mengajar Community Service Program: Strengthening Children’s Basic Literacy and Numeracy at Ransel Book - Misericordias Domini Domini; Aditya Putri Anugrahni; Olga Dona Retsi; Emeral Emeral (International Journal of Community Service (IJCS), 2026)
This community service program was implemented through PSM Mengajar, a non-formal learning activity conducted in collaboration between the author and the Student Choir Activity Unit (UKM Paduan Suara Mahasiswa) of Universitas Palangka Raya. This activity was carried out as a form of student contribution to supporting children’s education through a community-based learning space. The partner of this activity was Rumah Belajar dan Membaca Ransel Buku, located in Petuk Ketimpun, Jekan Raya District, Palangka Raya City. The program was conducted offline in four meetings on October 4, 11, and 25, and November 1, 2025. The target participants were 31 elementary school-aged children. The learning materials were arranged progressively, namely coloring in the first meeting, reading in the second meeting, writing in the third meeting, and arithmetic in the fourth meeting. Each meeting included ice-breaking activities such as singing and simple games to create an enjoyable learning atmosphere. The evaluation was conducted through documentation, facilitator notes, and internal committee reflection on the implementation process. This program indicates that community service based on student organizations can serve as a means of strengthening children’s literacy, numeracy, and creativity, as well as a social learning space for students to develop care, communication skills, and teaching experience in the community.